Experimental Research on Wave Changing of Rapid Assembling Anti-blast Walls. Issue 6 (March 2019) - Ge, Tao; Cao, Hongrui
Abstract: In order to research the ability to weaken the shock wave of the rapid assembling anti-blast walls, the shell explosion test was utilized to compare the shock wave overpressure peak in front of and behind the wall at different scaled distances. The overpressure suppression effect coefficient which reflects the wave dissipating performance of the anti-blast wall was put forward, and the effects of scaled distance, scaled wall height and scaled distance behind the wall on the wave dissipating performance were analysed with the experimental data. The results show that the value of reflected pressure is about 10 times the maximum value of diffraction overpressure, the scaled distance and the measuring distance behind the wall have a great effect on the diffraction overpressure; the diffraction overpressure behind the wall is significantly lower than the free field overpressure when there is no wall, and the overpressure suppression effect of the anti-blast wall can up to 50% or more; the scaled distance and the scaled wall height commonly affect the wave dissipating performance of the anti-blast wall. With the increase of the scaled distance behind the wall, the overpressure suppression effect coefficient gradually decreases. The research results can provide reference and basis for determining the safety distance of the target behind the anti-blast wall.